Cadre empowerment towards a zero waste lifestyle in Tanjung Pagar - Lena Rosida; Dewi Indah Noviana Pratiwi; Maria Ulfah; Mudrikah Khilda Noor; Kandria Firsta Salsabilla; M. Febriansyah (Universitas Muhammadiyah Magelang, 2024)
Tanjung Pagar sub-district is one of the sub-districts in Banjarmasin that still has residential areas along the riverbanks. Based on the observations of the service team, piles of rubbish were still found in several rivers in Tanjung Pagar Village. This situation indicates that there are still many people in this area who exhibit the behavior of throwing rubbish carelessly and have not been managing household waste properly. The aim of the activity is to enhance the knowledge and skills of Dasawisma women regarding the concept of zero waste and the utilization of waste for economic value. The method used involves education on waste management with the zero waste concept and training on converting inorganic waste into economically valuable goods. Partners' knowledge about waste management with the zero waste concept is assessed before and after education using a valid questionnaire. The results obtained from this program showed an increase in the average knowledge from 8.05 to 8.85 after education (p=0.002). Additionally, participants were also able to transform waste into economically valuable crafts.